The Effect of Different Amounts of Glycerol Fed to Lambs on Their Growth, Rumen Fermentation, Carcass Traits, Meat Characteristics, and Shelf Life - Uriel Hidalgo-Hernández; María Esther Ortega-Cerrilla; Pedro Zetina-Córdoba; José G. Herrera-Haro; José Vian (Agriculture)
Glycerol can effectively replace corn as an energy source in lamb diets without negatively impacting productive performance. This study evaluated the effects of substituting ground corn with different glycerol levels on the productive performance, ruminal fermentation, carcass characteristics, and meat quality at 24 h, 7, 14, and 21 d post-slaughter. A total of 40 male Suffolk × Hampshire crossbred lambs (25 ± 5 kg live weight) were used in a completely randomized design with four treatment groups (n = 10 each): 0% glycerol (GLY0), 5% glycerol (GLY05), 10% glycerol (GLY10), and 15% glycerol (GLY15). Including glycerol in the diet did not affect growth performance (p > 0.05). However, it did lead to an increase (p < 0.05) in the concentrations of NH3-N and the proportions of propionic and butyric acids, while the acetic acid levels decreased (p < 0.05). The backfat thickness, loin eye area (LEA), and carcass yield were not significantly affected (p > 0.05) by the addition of glycerol. Additionally, pH and color were also unaffected (p > 0.05), although the water-holding capacity showed a decrease (p < 0.05) over the shelf life of the meat. The chemical composition of the meat remained similar across all treatments, time points, and interactions (p > 0.05). In contrast, the protein content was significantly affected (p < 0.05) by the glycerol inclusion, time, and interactions between treatment and time. The results indicate that substituting up to 15% of ground corn with glycerol in lamb diets does not negatively impact productive performance, backfat thickness, LEA, carcass traits, or meat quality during shelf life. Throughout the shelf life, the crude protein concentrations and water-holding capacity decreased, while the propionic acid and NH3-N concentrations increased.